The Effects of Quinoa and Amaranth Flour on the Qualitative Characteristics of Gluten-Free Cakes - Razieh Hamzehpour; Asiye Ahmadi Dastgerdi (International Journal of Food Science)
The effect of pseudocereal flour such as quinoa and amaranth in different concentrations (0, 10, 20, and 30%) was investigated in gluten-free cake formulation. Cake containing amaranth and quinoa flour showed higher protein, fat, ash, and fiber content. A30 (30% amaranth) and Q30 (30% quinoa) had the highest values, and the control sample had the lowest values. The moisture content of the gluten-free cakes was not in the range of the Iranian standard. The sample containing 20% quinoa flour showed the highest specific volume (2.88±0.09 cm3/g) and the lowest hardness (259.33±10.09 g) (p<0.05). L∗ value varied from 72.09 to 79, and the gluten-free cakes had a darker color. All the cakes containing quinoa and amaranth flour showed low a∗ and b∗ values (p<0.05). Gluten-free cakes contain high amounts of unsaturated fatty acids (linoleic and linolenic acids) and minerals (iron, calcium, magnesium, and zinc). The results of the sensory evaluation showed that the sample containing 10% of amaranth and quinoa flour obtained the highest taste, aroma, color, appearance, and overall acceptability score compared to other treatments. In conclusion, it is possible to produce gluten-free cakes with quinoa and amaranth flour with sensory and physicochemical properties similar to wheat cakes. The formulations containing 20% and 30% quinoa were the best.